2007
DOI: 10.1590/s0004-27492007000400018
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory detection methods for methicillin resistance in coagulase negative Staphylococcus isolated from ophthalmic infections

Abstract: In the present study, we found that the E-test and the oxacillin salt agar screening test S (0.75 microg oxacillin per ml), when compared with polymerase chain reaction, were the most accurate currently available methods to phenotypically detect oxacillin resistance of coagulase negative Staphylococcus species. This study demonstrated that a good option for screening of ocular isolates for oxacillin resistance in the microbiology laboratory is the cefoxitin disk diffusion test and the automated Vitek system. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…7,13,14 The MR in frequently isolated staphylococci from ocular infections is a serious problem due to the difficulty in making appropriate treatment with antibiotics commonly used in ophthalmology. And also because associated with the MR is the cross-resistance to all beta-lactamics and to other antibiotics, such as cephalosporins, quinolones, and aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,13,14 The MR in frequently isolated staphylococci from ocular infections is a serious problem due to the difficulty in making appropriate treatment with antibiotics commonly used in ophthalmology. And also because associated with the MR is the cross-resistance to all beta-lactamics and to other antibiotics, such as cephalosporins, quinolones, and aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Oliveira et al reported that coagulase-negative methicillin-resistant Staphylococcus had in vitro resistance to multiple antibiotics used in ophthalmology. 7 Bacteria susceptibility to antimicrobials varies according to the socioeconomic factors at the individual and national levels either in developing or industrialized countries. 8 Emergence of resistant Staphylococcus from the conjunctiva is of great concern, because its virulence is related to the clinical outcome of ocular infections like keratitis or endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…This was a cross-sectional study in which the retrospective sample size was calculated by using PS software (Dupont & Plummer, 1997) using Dichotomous based on the sensitivity of the E-test and PCR at 100% and 98% respectively [41,42]. The Research and Ethics Committee, School of Medical Sciences, Universiti Sains Malaysia, approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of methicillin resistance has been reported greater in CoNS than in S. aureus, with rates ranging globally from 75% to 90% during the 1990s [14]. Most resistance to oxacillin in staphylococci is mediated by the mecA gene, which codes for the production of a supplemental penicillin-binding protein, which has a low affinity for b-lactam antibiotics [22]. Thus, they are clinically considered cefazolin resistant [27,34].…”
Section: Introductionmentioning
confidence: 99%